Reactive Oxygen Species-Mediated Cellular Stress Response and Lipid Accumulation in Oleaginous Microorganisms: The State of the Art and Future Perspectives - Shi, Kun; Gao, Zhen; Shi, Tian-Qiong; Song, Ping; Ren, Lu-Jing; Huang, He; Ji, Xiao-Jun (Frontiers in Microbiology, 2017)
Microbial oils, which are mainly extracted from yeasts, molds, and algae, have been of considerable interest as food additives and biofuel resources due to their high lipid content. While these oleaginous microorganisms generally produce only small amounts of lipids under optimal growth conditions, their lipid accumulation machinery can be induced by environmental stresses, such as nutrient limitation and an inhospitable physical environmental. As common second messengers of many stress factors, reactive oxygen species (ROS) may act as a regulator of cellular responses to extracellular environmental signaling. Furthermore, increasing evidence indicates that ROS may act as a mediator of lipid accumulation, which is associated with dramatic changes in the transcriptome, proteome, and metabolome. However, the specific mechanisms of ROS involvement in the crosstalk between extracellular stress signaling and intracellular lipid synthesis require further investigation. Here, we summarize current knowledge on stress-induced lipid biosynthesis and the putative role of ROS in the control of lipid accumulation in oleaginous microorganisms. Understanding such links may provide guidance for the development of stress-based strategies to enhance microbial lipid production.